Gender Inequality in India - Jain, Dr. Sudha (IJRDO - Journal of Social Science and Humanities Research, 2017)
The shortage of girls is more than a sociological concern; it demands that we change the mindset of doctors .The legacy of a declining sex ratio in the history of the Census of India has taken new turn with the widespread use of new reproductive technologies (NRTs) in urban areas. NRTs are based on the principles of selection of the desirable and rejection of the unwanted. In India, the desirable is the baby boy and the unwanted is the baby girl. The result is obvious; the Census of 2001 revealed that with a sex ratio of 933 women for every 1000 men, India had a deficit of 3.5 crore women when it entered the new millennium. To stop the abuse of advanced scientific techniques for selective elimination of female foetuses through sex -determination, the government of India passed the Pre-natal Diagnostic Techniques (PNDT) Act in 1994. But techno-docs based in the metropolises & other urban centres, and parents desirous of begetting only sons, have subverted it.